A pragmatics analysis on commanding utterances in animation movie manuscript - Rismawati, Rismawati, Drs. Agus Wijayanto M.A., Ph.D, Drs. Sigit Haryanto, M.Hum (2014)
This research aims at describing the linguistics form, the strategies and the politeness strategies of commanding utterances in "Tangled" animation movie manuscript. The research method applied in this study is qualitative approah. The results of the research show that firstly, the linguistics forms of commanding utterances found in Tangled animation movie manuscript of them are declarative, positive imperative, negative imperative, imperative using Let's, interrogative, combination, assuring, asking a help, asking for attention, arranging strategy, continuing adventure, getting angry, motivating, prohibiting, to make someone in hurry, warning, and worrying. Secondly, the strategies of commanding utterances found in the "Tangled" animation movie are positive imperative and imperative sentence using let's. Thirdly, the politeness strategies of commanding utterances found in the "Tangled" animation movie are 1) the other-directed command uses both bald-on record and positive politeness, and 2) the self-directed command only uses bald-on record.